The Role of e-Governance in Improving Local Governments Performance (Case Study: Sumbawa Regency) - Kurniawan, Cahyadi; Pribadi, Ulung; Iqbal, Muhammad (Jurnal Ilmiah Peuradeun, 2023)
This research focused on how technology could help improve local government performance. There are five factors in assessing the IT capacity of information; security, financial support, legislative support, and commitment to the organization. Many variables affect the ability to support the five characteristics. The population of this study was all work units responsible for the local government's performance in Sumbawa Regency, West Nusa Tenggara Province, Indonesia. The sample was randomly selected to assess the effect of e-government in improving local government performance. Every year the work unit must report to the region. Regression analysis was employed in this study by using SEM-PLS software. The data showed that the variables of executive competence, financial Support, information security, legislative Support, and organizational commitment affected information capacity by 59.4%. The function of e-government in improving local government performance must be realized. For e-government to improve the performance of local governments, the two provincial/central governments must conduct socialization with local governments. Limitations of the study included the limited sample size, which might not represent the original status of citizens, and the short study period.